Early acute kidney injury is associated with in-hospital adverse outcomes in critically ill burn patients: an observational study - Martins J. (2023)
BACKGROUND: There are no studies in large series of burn patients on the relationship between acute kidney injury (AKI) and adverse outcomes using the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. METHODS: We retrospectively analysed data from a cohort of burn patients admitted to the intensive care unit (ICU) with the diagnosis of burn injury. The diagnosis of AKI over the first 7 days after injury was made according to the KDIGO guidelines. The primary outcome was ICU mortality. We used estimative models using univariable and multivariable logistic regression analyses. RESULTS: A total of 960 patients were studied and AKI was diagnosed in 50.5%. In multivariable analysis, AKI was associated, as compared with patients without AKI, with ICU mortality {adjusted odds ratio [aOR] 2.135 [95% confidence interval (CI) 1.384-3.293]} and secondary outcomes [kidney replacement therapy, aOR 4.030 (95% CI 1.838-8.835); infection, aOR 1.437 (95% CI 1.107-1.866); hospital mortality, aOR 1.652 (95% CI 1.139-2.697)]. AKI stage 1 was associated with a higher ICU [aOR 1.869 (95% CI 1.183-2.954)] and hospital mortality [aOR 1.552 (95% CI 1.050-2.296)] and infection [aOR 1.383 (95% CI 1.049-1.823)]. AKI meeting the urine output (UO) criterion alone was not associated with increased mortality. Ignoring the UO criterion would have missed 50 (10.3%) cases with AKI. CONCLUSION: The KDIGO guidelines are useful to diagnose AKI in burn patients. Even the mild form of AKI is independently associated with increased mortality. Considering the UO criterion is important to more accurately assess the incidence of AKI, but AKI meeting the UO criterion alone is not associated with increased mortality.